Humanistična avlična satira - Bogataj, Jan Dominik (Keria (Ljubljana), 2024)
The article examines De miseriis curialium, written in 1444 by Enea Silvio Piccolomini, which critically exposes the moral and social corruption of 15th-century royal courts. The work belongs to the tradition of anti-court literature, dating from antiquity to the Middle Ages, and portrays the court as a place of hypocrisy, envy, and manipulation. The central motifs include wine, symbolizing the empty promises of courtly life; envy, which destroys interpersonal relationships; and contempt for intellectuals, as the court does not encourage knowledge but rewards scheming incompetence. Piccolomini emphasizes that the court leaves no room for true friendship or moral integrity. The author places the work within the broader context of humanist thought and highlights its influence on later literature. De miseriis curialium goes beyond mere historical critique, offering a deeper reflection on power, morality, and human nature, which keeps it relevant even today.
Keywords: anti-court literature; humanism; humanizem; intelektualci; intellectuals; moral critique; moralna kritika; oblast; power; protiavlična literatura; satira; satire